Intersection of ESG performance and corporate innovation: a perspective of vertical linkages within the industrial chain - Jian, Zhu; Guanghua, Xu; Xiaodong, Li (Frontiers in Sustainability, 2025)
Developing a more innovative industrial and supply chain is crucial for enhancing national selfreliance in innovation capabilities. This study aims to investigate the relationship between corporate ESG performance and innovation within supply chain enterprises, revealing the transmission mechanism of ESG along the supply chain. Utilizing data from Chinese A-share listed companies from 2009 to 2022, this research employs a fixed-effects model to analyze the impact of corporate ESG ratings on the innovation quality of both upstream and downstream firms in the supply chain. To address potential endogeneity concerns, the instrumental variables approach is applied. Mechanism tests are conducted to identify potential mediating channels, followed by heterogeneity analysis to explore the boundary conditions of the ESG impact. The findings indicate that a higher corporate ESG rating is significantly associated with improved innovation quality in customer firms. However, this positive effect is not observed in supplier firms. Mechanism tests suggest that firms primarily enhance their customers’ innovation through pathways such as ESG spillovers, innovation knowledge spillovers, improved supply chain efficiency, alleviated financing constraints, and reduced agency costs. These results imply an asymmetry in the influence of corporate ESG performance, likely shaped by the power structure and direction of knowledge flow within the supply chain. Overall, this study provides a novel perspective for understanding corporate innovation and supply chain collaboration. It offers valuable policy iplications for China’s efforts to enhance supply chain integration and innovation, suggesting that encouraging and supporting stronger corporate ESG practices can help activate innovation vitality across the entire supply network.